Chunking a Transcription of a Lecture to Help Students at EAP Courses Improve their Listening Comprehension Skill(S) - Janusz Badio (Research in Language)
Pre-sessional EAP courses in the UK welcome international students seeking admission to British universities. The official requirement for English language proficiency is typically determined by a student’s scores in the four language skills. Students' proficiency levels in these skills generally range from 5.0 to 6.5. One significant challenge faced by foreign students is in the area of listening skills. The listening comprehension classes often involve listening to lengthy lectures, during which students struggle with note-taking and answering questions. One effective instructional strategy is to provide plain text transcripts of recorded lectures. This article aims to illustrate how a lecturer segments speech and how teachers can transcribe this process and its constituent units using methodologies discussed in works such as Badio (2004), Chafe (1994, 2003), and Croft (1995). The unit of speech in these analyses is defined by a set of conceptual and phonetic criteria, and segmenting a lecture involves applying these criteria impressionistically. The resulting modified format of a plain text transcript can serve as a valuable pedagogical tool. Teachers can demonstrate to students, who may not have a background in linguistics, that a single word is not the only or primary unit of speech. They can illustrate how pauses signal new topics or how different types of intonation units are used to convey conceptualisations and regulate the flow of ideas and speech. Such focused and structured presentations enhance language acquisition and learning.